Slit-Enhanced Chiral- and Broadband Infrared Ultra-Sensing - Knipper, Richard; Kopecky, Vladimir; Huebner, Uwe; Popp, Juergen; Mayerhoefer, Thomas G. (ACS Photonics, 2018)
This work demonstrates a membrane-based chiral plasmonic metamaterial with two plasmonic absorption bands which can be used for broadband surface-enhanced infrared absorption (SEIRA) and vibrational circular dichroism (VCD) sensing in the spectral range ∼1000-4000 cm-1 (SEIRA) and ∼2000-4000 cm-1 (VCD). Based on finite-difference time-domain simulations, the chiral plasmonic response was optimized for enhancement at around 3200 cm-1. Accordingly, the chiral cross-slit array was adjusted for application in conventional transmission measurement setups and covers an area of 1 mm2. Polyethylene was used as a model analyte to simulate the SEIRA broadband response and the results were compared with octadecanethiol measurements due to their spectral similarity. Signal enhancement was observed from 3000 cm-1 down to 1400 cm-1 by tuning the polarization of the incoming radiation. Due to the inherent chirality of the design, a strong VCD absorbance of 0.83 at ∼3500 cm-1 could be observed for the unloaded substrate. For substrates loaded with α-pinene, it was observed that this value even increased to more than unity and, in addition, direct enhancement of VCD could be achieved, although the VCD signal is not directly comparable with that of the neat substance. Since the substrate-analyte complex also shows a giant circular birefringence effect, most likely due to the formation of a chiral effective medium, it has great potential to be used as a sensor and may be applicable in a multitude of different scenarios in the analysis of biologic and pharmaceutic substances.
CRIS-Team Scopus Importer:2023-04-20
Keywords: chiral plasmonics; infrared spectroscopy; metamaterials; surface enhancement; vibrational circular dichroism